Peer Tutor-Based Quranic Learning in Elementary Schools - Muhammad Irfan (FASHLUNA, 2026)
The peer tutoring method aims to provide students with greater freedom and opportunities to interact freely and reduce their perceived inadequacy towards their teachers. This is especially true in terms of reading and writing the Quran well and correctly. The research method used is qualitative with a library research approach , also known as literature study, with data analysis using content analysis. The peer tutoring method is deemed essential to improve students' ability to read and write the Quran well and correctly and foster students' enthusiasm for studying the Quran. The implementation of the peer tutoring method must go through stages, namely preparation, implementation, and evaluation stages. In implementing the peer tutoring method, there are three series of activities that must be followed: initial activities, core activities, and final or closing activities. By implementing this peer tutoring method, students become enthusiastic and motivated to continue developing their ability to read and write the Quran well and correctly.